A Conceptual Study on the Role of Vasa Bhavit Haridra Churnam in Vataja Kasa (Dry Cough) w.s.r. to Allergic Bronchitis: A Review - Surendra Kumar,; Megha Murali,; Sujeet Kumar, (International Journal of Ayurveda and Pharma Research, 2022)
In the present era of COVID -19, management of respiratory disorders is becoming a challenge to the world. Ayurveda, the science of life, provides a lot of hope in the present condition by assuring better results in the field of prevention and management of respiratory diseases. Cough carries out an essential protective function for the respiratory tract and lungs. Kasa (cough) is one of the commonest complaints in day-to-day life and it is also a symptom of various diseases of the respiratory system. In Ayurveda, Acharyas have explained Kasa in detail. They have described five types of Kasa. Among the various respiratory diseases, Vataja Kasa (dry cough) has been selected here. In the contemporary science, it can be correlated to Allergic Bronchitis, which is one of the common problems throughout the world. In the present study Vasa Bhavit Haridra Churnam (VBHC) has been selected from Siddh Bhaisajya Manimala and further details regarding the ingredients were collected from various text books, PubMed, research articles, previous works done etc. As per the data collected, Allergic Bronchitis when treated with Vasa Bhavit Haridra Churnam will be effective in relieving the symptoms. Ayurveda has a vital role to play in the field of respiratory ailments.